2012
DOI: 10.1111/j.1467-9817.2012.01543.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual‐attentional span and lexical ­decision in skilled adult readers

Abstract: The goal of the study was to examine the association between visual‐attentional span and lexical decision in skilled adult readers. In the span tasks, an array of letters was presented briefly and recognition or production of a single cued letter (partial span) or production of all letters (whole span) was required. Independently of letter recognition and phoneme awareness, width of partial recognition span predicted substantial variance only in detection of letter misorderings in words, while partial span eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Second, the deficit when observed in the whole report condition was also found in partial report (Bosse et al, 2007;Valdois et al, 2021;Zoubrinetzky et al, 2014) and scores on the two tasks were highly correlated (correlation coefficients varying from .44 to .71; Bosse et al, 2007;Bosse & Valdois, 2009;Chan & Yeung, 2020;C. Chen et al, 2016;Holmes & Dawson, 2014;Valdois et al, 2021;Zoubrinetzky et al, 2014).…”
Section: Behavioural Evidence From Alphanumeric Stringsmentioning
confidence: 85%
See 2 more Smart Citations
“…Second, the deficit when observed in the whole report condition was also found in partial report (Bosse et al, 2007;Valdois et al, 2021;Zoubrinetzky et al, 2014) and scores on the two tasks were highly correlated (correlation coefficients varying from .44 to .71; Bosse et al, 2007;Bosse & Valdois, 2009;Chan & Yeung, 2020;C. Chen et al, 2016;Holmes & Dawson, 2014;Valdois et al, 2021;Zoubrinetzky et al, 2014).…”
Section: Behavioural Evidence From Alphanumeric Stringsmentioning
confidence: 85%
“…Group studies reported small to no correlations between performance on verbal STM and oral VAS tasks in dyslexic individuals (C. Chen, Schneps, Masyn, & Thomson, 2016; Cheng et al, 2021). Second, the deficit when observed in the whole report condition was also found in partial report (Bosse et al, 2007; Valdois et al, 2021; Zoubrinetzky et al, 2014) and scores on the two tasks were highly correlated (correlation coefficients varying from .44 to .71; Bosse et al, 2007; Bosse & Valdois, 2009; Chan & Yeung, 2020; C. Chen et al, 2016; Holmes & Dawson, 2014; Valdois et al, 2021; Zoubrinetzky et al, 2014). Although no study provided a direct comparison of performance in the whole and partial report tasks, similar levels were typically reported, or slightly higher performance in partial report (Bosse et al, 2007; Bosse & Valdois, 2009; Saksida et al, 2016; Zoubrinetzky et al, 2014, 2016).…”
Section: Is Vas Performance a Marker Of Verbal Processing?mentioning
confidence: 88%
See 1 more Smart Citation